Barriers to Optimal Tuberculosis Treatment Services at Community Health Centers: A Qualitative Study From a High Prevalent Tuberculosis Country - Pradipta, Ivan S.; Idrus, Lusiana R.; Probandari, Ari; Puspitasari, Irma Melyani; Santoso, Prayudi; Alffenaar, Jan-Willem C.; Hak, Eelko (Frontiers in Pharmacology, 2022)
Background: Community health centres (CHCs) are a backbone health-care facility for tuberculosis (TB) services. Identifying barriers amongst TB service providers at the CHC level is required to help them deliver successful TB treatment. Aims: The current study aimed to analyse barriers to successful TB treatment from the perspective of TB service providers in a high prevalent TB country. Methods: A qualitative study was conducted using in-depth interviews and focus group discussions in a province of Indonesia with a high TB prevalence. Two districts representing rural and urban areas were selected to obtain information from TB service providers (i.e., physicians and nurses) at the CHC level. In addition, key informant interviews with TB patients, hospital TB specialists, pharmacists and activists were conducted. The trustworthiness and credibility of the information were established using information saturation, participant validation and triangulation approaches. The interviews were also transcribed for the inductive analysis using Atlas ti 8.4 software. Results: We identified 210 meaning units from 48 participants and classified them into two main themes: organisational capacity and TB programme activities. We identified the inadequacy of human resources, facility and external coordination as the main barriers to organisational capacity. Furthermore, the barriers were identified regarding TB programme activities, i.e., inadequate TB case finding, diagnosis, drug supply chain and dispensing management, treatment and monitoring, case recording and reporting and public-private collaboration. Conclusion: Strengthening CHCs in the management of TB is critical to reaching the national and global goals of TB eradication by 2035. These findings can be considered to develop evaluation strategies to improve the successful TB treatment in high prevalent TB countries, especially Indonesia.